PEMANFAATAN AI UNTUK MENDUKUNG KINERJA PEGAWAI KANTOR DESA KLAMBIR V - Reza Alamsyah; Niko Surya Atmaja (PT. Ndruru Jaya Mandiri, 2026)
The Klambir V Village Office faces challenges in meeting the increasing demand for fast, accurate, and efficient public services. However, limited digital competence and minimal utilization of Artificial Intelligence (AI) technology cause administrative processes, such as drafting letters, reports, and managing information, to consume a relatively long time. This Community Service (PKM) activity aims to enhance the knowledge, understanding, and skills of 12 village officials through socialization and training on the productive, safe, and responsible use of AI-based applications. The implementation method includes preparation, theoretical material presentation, practical workshop on AI tools, interactive discussions, and direct mentoring. The results of this activity indicate an increase in the digital capacity of village officials in mitigating administrative constraints, shortening the duration of drafting operational documents, and accelerating digital transformation within the village government bureaucracy to achieve optimal public services.